Research Note: Reticulocytes and related erythroid atypia of ducks—indicators of stress or pathology? - Paul F. Cotter (Poultry Science, 2024)
ABSTRACT: Two kinds of reticulocytes, and atypical erythroid cells, were found in the blood of apparently healthy ducks with Wright–Giemsa (W–G) stain. The reticulin of network-type examples (nRtc) is of a large complex (3-D) form. The punctate reticulocyte (pRtc) contains small pin-point cytoplasmic granulations; both cells are distinct from a polychromatic RBC (pRBC). Atypical erythroid cells with oval or irregular shapes reminiscent of primary or yolk-sac RBCs (ysRBC) accompanied the Rtc. Rare binuclear cells (bi) were either polychromatic (pRBC and pRtc) or full hemoglobin (Hb) types (RBC). Some bi with equal-sized daughter nuclei were presumed mitotic products. Conversely, unequal daughter nuclei were amitotic products, a nuclear division without chromosomes or a spindle. Erythrocytes formed tight aggregations with thrombocytes or other cells called “toroids”; further indicating a reactive hemogram. Erythroplastids (ep) anuclear erythroid cells, found along with other atypia, were either pRBC or full Hb types. The total white blood counts (TWBC) of the study set ranged from 5 K/μL (embryo E [d24]) to >100 K/μL (older ducks) with heterophil ratios (H/L) ranging from 0.5 to >4.0. Atypical erythroid cells, like atypical leukocytes, indicate a transition from homeostasis to a reactive state. Recognition of nRtc, pRtc, and toroids as reactive forms, expands the utility of hematologic data in assessing stress levels, indicating pathology, and exploring welfare questions. The present observations support earlier work showing some reticulocytes are detected by W–G alone and do not require vital dyes. Cells and behaviors described here demonstrate the benefit that a description of overall cytology adds to H/L ratios in evaluating a hemogram.